PENGARUH BUDAYA ORGANISASI DAN KEPUTUSAN PENDANAAN TERHADAP KINERJA KEUANGAN PADA KOPERASI DI DENPASAR - Agus Putra Mardika (Nusantara Hasana Journal, 2022)
This study aims to explain the effect of funding decisions on organizational culture, explain the influence of organizational culture on financial performance, explain the effect of funding decisions on financial performance. This research was conducted at a cooperative in Denpasar. Financial performance is an analysis carried out to see how far the company has carried out supervision by using financial implementation rules properly and correctly. Financial performance in this study is influenced by funding decisions and organizational culture. The culture that develops and is applied to the organization or company can influence decisions taken by management or company owners related to the use of external funding sources that can affect financial performance. Data analysis was performed using PLS (partial least square). The results of this study indicate that organizational culture has a positive and insignificant effect on funding decisions, organizational culture has a positive and significant influence on financial performance and funding decisions have a negative and significant influence on financial performance.